2020
DOI: 10.1158/0008-5472.can-19-1684
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β-Catenin Cooperates with Loss of Pten to Drive AR-Independent Castration-Resistant Prostate Cancer

Abstract: Inhibition of the androgen receptor (AR) is the main strategy to treat advanced prostate cancers. AR-independent treatmentresistant prostate cancer is a major unresolved clinical problem. Patients with prostate cancer with alterations in canonical WNT pathway genes, which lead to b-catenin activation, are refractory to AR-targeted therapies. Here, using clinically relevant murine prostate cancer models, we investigated the significance of b-catenin activation in prostate cancer progression and treatment resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…At the same time, WNT/β-catenin signaling pathway is highly activated in AR negative PCa (Wan et al, 2012). A growing body of evidence supports the hypothesis that WNT/β-catenin signalling pathway promotes metastatic castration-resistant prostate cancer (mCRPC) by a complex interaction with AR signalling (Patel et al, 2020; Ramamurthy et al, 2018; Schweizer et al, 2008; Tsao et al, 2021). WNT/β-catenin axis is a known positive regulator of PCa metastatic dissemination (Patel et al, 2020) and treatment resistance (Yeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, WNT/β-catenin signaling pathway is highly activated in AR negative PCa (Wan et al, 2012). A growing body of evidence supports the hypothesis that WNT/β-catenin signalling pathway promotes metastatic castration-resistant prostate cancer (mCRPC) by a complex interaction with AR signalling (Patel et al, 2020; Ramamurthy et al, 2018; Schweizer et al, 2008; Tsao et al, 2021). WNT/β-catenin axis is a known positive regulator of PCa metastatic dissemination (Patel et al, 2020) and treatment resistance (Yeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AR is in fact a WNT/β-catenin target gene, and AR and β-catenin can directly interact and co-localize in the nucleus to mediate transcriptional activity of AR-regulated genes [ 328 , 329 , 330 ] ( Figure 1 ). WNT and AR signaling cascades have also been shown to reciprocally inhibit each other in murine prostate cancer [ 331 ].…”
Section: The Pi3k-akt-mtor Pathway Intersects With Multiple Oncogementioning
confidence: 99%
“…Mouse models have been instrumental in determining the role of WNT signaling in prostate cancer, and we and others have shown that constitutive activation of β-catenin or Apc bi-allelic deletion predisposes to prostate adenocarcinoma in mice [ 269 , 331 , 332 , 333 ]. Moreover, β-catenin activation can cooperate with Pten heterozygous or homozygous deletion to promote prostate cancer progression, CRPC transition and metastatic potential [ 269 , 331 , 332 , 333 ], indicating a synergistic relationship exists between the PI3K-AKT-mTOR and WNT cascades.…”
Section: The Pi3k-akt-mtor Pathway Intersects With Multiple Oncogementioning
confidence: 99%
See 1 more Smart Citation
“…β-catenin activation and PTEN deletion synergistically drive non-AR independent castrationresistant prostate cancer. [24][25][26] In most cancer types, the PI3K signaling pathway is activated and promotes tumorigenesis by regulating nutrient metabolism, cell proliferation, survival, migration, and angiogenesis. 26 The potential mechanism of PI3K/AKT activation is mainly due to the deletion or mutation of its key negative regulatory gene, PTEN.…”
Section: Dovepressmentioning
confidence: 99%